Analisis Pengaruh Implementasi Nilai-Nilai Tri Hita Karana Oleh Kepala Sekolah terhadap Kualitas Hubungan Antarwarga Sekolah - Wayan Eka Swarjawa, I; B. Arnyana, I.; Wayan Suja, I (Journal of Comprehensive Science, 2025)
This research is purposed to investigate the implementation of Tri Hita Karana values by the principal on the quality of relationships among school members at SD Negeri 1 Kenderan. The population of this study consists of the principal, teachers, educational staff, and students of SD Negeri 1 Kenderan. The sampling technique used was purposive sampling to ensure that the research subjects had sufficient knowledge or experience regarding the implementation of Tri Hita Karana. Proportionate stratified random sampling was applied to ensure the representation of each group in the sample, namely the principal, teachers, educational staff, and students. The total sample in this study was 70 participants, consisting of 1 principal, 8 teachers, 1 educational staff member, and 60 students. Data collection methods included surveys, observations, and document reviews of supporting evidence. The instrument used to collect data was a questionnaire. The data was collected would be analyzed by using descriptive statistical analysis and inferential statistical analysis (simple linear regression). Based on the data analysis, the average score of each questionnaire item was 4, categorized as good. The result showed tobserved = 3.896 > ttable = 1.995 at the significance level 5%. Therefore, it can be concluded that the implementation of Tri Hita Karana values by the principal has a significant influence on the quality of relationships among school members at SD Negeri 1 Kenderan. The influence is positive, with a regression coefficient of 0.433. The contribution of the implementation of Tri Hita Karana values by the principal to the quality of relationships among school members at SD Negeri 1 Kenderan is 18.3%. This indicates that the application of these values can foster a sense of togetherness, mutual respect, and harmony in the interactions among school members.